HACCP implementation and economic optimality in turkey processing - Nganje, W.E.; Kaitibie, S.; Sorin, A. (Wiley, 2007)
Regulatory impact assessment suggests that Hazard Analysis and Critical Control Points (HACCP) is a cost-effective food safety regulation that is highly beneficial to society. This study focuses on firm-level costs and benefits from adoption of specific critical control points. A stochastic optimization framework is used to determine optimal testing and sampling strategies for Salmonella reduction in turkey processing. Results show that under The Food Safety Inspection Service (FSIS) mandated tolerance levels, processors need to designate no more than five critical control points, three more than what is included in the generic HACCP plan. Moves to tighten tolerances should be considered carefully because additional implementation costs tend to increase exponentially.